Methods Used to Maximize Follow-Up: Lessons Learned From the Therapeutic Hypothermia After Pediatric Cardiac Arrest Trials*. Issue 1 (January 2020) - Gildea, Marianne R.; Moler, Frank W.; Page, Kent; Meert, Kathleen; Holubkov, Richard; Dean, J. Michael; Christensen, James R.; Slomine, Beth S.
Abstract : Objectives: To describe telephone interview completion rates among 12-month cardiac arrest survivors enrolled in the Therapeutic Hypothermia after Pediatric Cardiac Arrest In-Hospital and Out-of-Hospital trials, identify key characteristics of the completed follow-up interviews at both 3- and 12-month postcardiac arrest, and describe strategies implemented to promote follow-up. Setting: Centralized telephone follow-up interviews. Design: Retrospective report of data collected for Therapeutic Hypothermia after Pediatric Cardiac Arrest trials, and summary of strategies used to maximize follow-up completion. Patients: Twelve-month survivors ( n = 251) from 39 Therapeutic Hypothermia after Pediatric Cardiac Arrest PICU sites in the United States, Canada, and United Kingdom. Interventions: Not applicable. Measurements and Main Results: The 3- and 12-month telephone interviews included completion of the Vineland Adaptive Behavior Scales, Second Edition. Vineland Adaptive Behavior Scales, Second Edition data were available on 96% of 3-month survivors (242/251) and 95% of 12-month survivors (239/251) with no differences in demographics between those with and without completed Vineland Adaptive Behavior Scales, Second Edition. At 12 months, a substantial minority of interviews were completed with caregivers other than parents (10%), after calls attempts were made on 6 or more days (18%), and during evenings/weekends (17%). Strategies included emphasizing the relationship between study teams and participants, ongoing communication between study team members across sites, promoting site engagement during the study's final year, and withholding payment for work associated with the primary outcome until work had been completed. Conclusions: It is feasible to use telephone follow-up interviews to successfully collect detailed neurobehavioral outcome about children following pediatric cardiac arrest. Future studies should consider availability of the telephone interviewer to conduct calls at times convenient for families, using a range of respondents, ongoing engagement with site teams, and site payment related to primary outcome completion. Abstract : Supplemental Digital Content is available in the text.